2007
DOI: 10.1097/01.ccm.0000281859.61545.22
|View full text |Cite
|
Sign up to set email alerts
|

Does the prognosis of cardiac arrest differ in trauma patients?*

Abstract: The survival and neurologic outcome of out-of-hospital cardiac arrest were not different between trauma and medical patients. This result suggests that, under the supervision of senior physicians, active resuscitation after out-of-hospital cardiac arrest is as important in trauma as in medical patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
20
1
5

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(32 citation statements)
references
References 33 publications
6
20
1
5
Order By: Relevance
“…These results also support our thesis that active CPR attempts after pre-hospital cardiac arrest may be as important in trauma patients as in medical patients, in particular if senior physicians are involved in patient's care [18]. Pickens et al showed a discharge rate of 7.6% in patients with trauma-related cardiac arrest, and further criticized recommendations that suggest not to perform CPR attempts in trauma patients [19].…”
Section: Resultssupporting
confidence: 79%
See 2 more Smart Citations
“…These results also support our thesis that active CPR attempts after pre-hospital cardiac arrest may be as important in trauma patients as in medical patients, in particular if senior physicians are involved in patient's care [18]. Pickens et al showed a discharge rate of 7.6% in patients with trauma-related cardiac arrest, and further criticized recommendations that suggest not to perform CPR attempts in trauma patients [19].…”
Section: Resultssupporting
confidence: 79%
“…In the present study, trauma patients were 15 years younger compared with patients with cardiac causes, and the proportion of patients aged over 60 years was 45% compared with 72% younger than 60 years. This difference in age was also found by David et al [18]. The location of cardiac arrest also differed.…”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…Many patients without severe injuries that have been triaged in the field by physicians are directly sent to the emergency department rather than to the Trauma Resuscitation Unit, which forms our study cohort. 24 …”
Section: Discussionmentioning
confidence: 99%
“…In practice, these patients are very seriously injured, and a few were already in cardiac arrest. As only around 2% of patients with traumatic cardiac arrest survive to discharge, many of these patients are likely to die 11. The true number of secondary transfers required therefore may be less than our estimate (figures 2 and 3).…”
Section: Resultsmentioning
confidence: 57%